Zfp281 Inhibits the Pluripotent-to-Totipotent State Transition in Mouse Embryonic Stem Cells - Wen, Xinpeng; Lin, Zesong; Wu, Hao; Cao, Lanrui; Fu, Xudong (Frontiers in Cell and Developmental Biology, 2022)
The cell-fate transition between pluripotent and totipotent states determines embryonic development and the first cell-lineage segregation. However, limited by the scarcity of totipotent embryos, regulators on this transition remain largely elusive. A novel model to study the transition has been recently established, named the 2-cell-like (2C-like) model. The 2C-like cells are rare totipotent-like cells in the mouse embryonic stem cell (mESC) culture. Pluripotent mESCs can spontaneously transit into and out of the 2C-like state. We previously dissected the transcriptional roadmap of the transition. In this study, we revealed that Zfp281 is a novel regulator for the pluripotent-to-totipotent transition in mESCs. Zfp281 is a transcriptional factor involved in the cell-fate transition. Our study shows that Zfp281 represses transcripts upregulated during the 2C-like transition via Tet1 and consequentially inhibits mESCs from transiting into the 2C-like state. Interestingly, we found that the inhibitory effect of Zfp281 on the 2C-like transition leads to an impaired 2C-like-transition ability in primed-state mESCs. Altogether, our study reveals a novel mediator for the pluripotent-to-totipotent state transition in mESCs and provides insights into the dynamic transcriptional control of the transition.